Patient-Specific Carbon Nanocomposite Tracheal Prosthesis. Issue 1 (January 2015) - Chua, Matthew; Chui, Chee-Kong; Teo, Constance; Lau, David
Purpose: Surgical removal of the trachea is the current gold standard for treating severe airway carcinoma and stenosis. Resection of 6 cm or more of the trachea requires a replacement graft due to anastomotic tension. The high failure rates of current grafts are attributed to a mismatching of mechanical properties and slow epithelium formation on the inner lumen surface. There is also a current lack of tracheal prostheses that are closely tailored to the patient's anatomy. Methods: We propose the development of a patient-specific, artificial trachea made of carbon nanotubes and poly-di-methyl-siloxane (CNT-PDMS) composite material. Computational simulations and finite element analysis were used to study the stress behavior of the designed implant in a patient-specific, tracheal model. Results: Finite element studies indicated that the patient-specific carbon nanocomposite prosthesis produced stress distributions that are closer to that of the natural trachea. In vitro studies conducted on the proposed material have demonstrated its biocompatibility and suitability for sustaining tracheal epithelial cell proliferation and differentiation. In vivo studies done in porcine models showed no adverse side effects or breathing difficulties, with complete regeneration of the epithelium in the prosthesis lumen within 2 weeks. Conclusions: This paper highlights the potential of a patient-specific CNT-PDMS graft as a viable airway replacement in severe tracheal carcinoma.